磁共振转运培养箱用于新生儿头颅磁共振检查的多中心前瞻性随机对照研究 (Zhongguo Dang Dai Er Ke Za Zhi, 2020)
OBJECTIVE: To study the safety and efficacy of magnetic resonance imaging (MRI)-compatible incubator in cranial MRI examination for neonates. METHODS: A total of 120 neonates who were hospitalized in three hospitals and needed to undergo MRI examination were randomly divided into a control group and an experimental group, with 60 neonates in each group. The neonates in the experimental group were transferred with MRI-compatible incubator and underwent cranial MRI examination inside the MRI-compatible incubator, and those in the control group were transferred using a conventional neonatal transfer incubator and then underwent MRI examination outside the incubator. The two groups were compared in terms of the primary efficacy index (total examination time), secondary efficacy indices (times of examination, MRI completion rate on the first day of use), and safety indices (incidence rate of adverse events and vital signs). RESULTS: There were no significant differences in total examination time, times of examination, and MRI completion rate on the first day of use between the two groups (P > 0.05). There were also no significant differences between the two groups in the incidence rate of adverse events and vital signs such as respiratory rate, heart rate, blood pressure, and blood oxygen saturation rate at different time points before and after examination (P > 0.05). CONCLUSIONS: The use of MRI-compatible incubator does not significantly shorten the examination time of cranial MRI, but it does provide a relatively stable environment for examination with acceptable safety. There is a need for further studies with a larger population.